VD_FINDINFO HC / 2017 / 395 vom 29. Mai 2017 - VD Tribunal cantonal (2017)
CONTRAT D'ENTREPRISE, NORME SIA, PRIX FERME, EXPERTISE, EXÉCUTION PERSONNELLE | 366 al. 2 CO, 373 CO, 374 CO, 308 al. 1 let. a CPC (CH)